Development strategy of culinary business employing the Blue Ocean Strategy (BOS) - Ardian, S; Syairudin, B (IPTEK Journal of Proceedings Series, 2018)
Culinary business development is now growing quite rapidly, Surabaya became one of the target markets of domestic and foreign businessmen in culinary business. The high competition in the culinary business is a powerful reason to apply the right business strategy to be able to survive and win the competition. One of the method that can be used in offering business strategy is the Blue Ocean Strategy (BOS). By identifying the strengths, weaknesses, opportunities and threats (SWOT) of the business strategy and then designing the blue ocean strategy which is taken as a metaphor to represent these industries that may offer greater opportunity or higher profit potential. This is the goal of blue ocean strategy, to search for and gain unexplored market space instead of engage in traditional competition. The object of observations in this study is spicy noodle business. This study aimed atdeveloping a business strategy formulation with BOS and providing alternative solutions for business development to the management that agree with the socio-cultural conditions of Surabaya. The results showed that there are two strategies that should be eliminated, like the strategiesof offeringfranchise without royalty fees and no separation of smoking and non-smoking area. There are three strategies that should be reduced, such as reducing educative wall posters, reducting door prizes and photo contest, and reducing the amount of franchise. There are six strategies that can be improved, namely increasing serving time, being efficient of tables arrangement, providing employment for local residents, strategic location closes to several colleges, photobooth (selfie corner) for consumers and increasing the uniquenessconcept of the shop. The alternative solutions of business development can be done by adding facilities such as Wi-Fi connection and air conditioning (AC) installationto comfort theconsumers,guest comment (online and offline suggestion box), and membership (visitors’ ID).